Lactic acid production from waste sugarcane bagasse derived cellulose - Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2007)
Production of L(+) lactic acid from sugarcane bagasse cellulose, one of the abundant biomass materials available in India, was studied. The bagasse was chemically treated to obtain a purified bagasse cellulose sample, which is much more amenable to cellulase enzyme attack than bagasse itself. This sample, at high concentration (10%), was hydrolyzed by cellulase enzyme preparations (10 FPU g(-1) cellulose) derived from mutants generated in our own laboratory. We obtained maximum hydrolysis (72%), yielding glucose and cellobiose as the main end products. Lactic acid was produced from this bagasse cellulose sample by simultaneous saccharification and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus delbrueckii mutant Uc-3. A maximum lactic acid concentration of 67 g l(-1) was produced from a concentration of 80 g l(-1) of bagasse cellulose, the highest productivity and yield being 0.93 g l(-1) h(-1) and 0.83 g g(-1), respectively. The mutant Uc-3 was found to utilize high concentrations of cellobiose (50 g l(-1)) and convert it into lactic acid in a homo-fermentative way. Considering that bagasse is a waste material available in abundance, we propose to valorize this biomass to produce cellulose and then sugars, which can be fermented to products such as ethanol and lactic acid.